Seksualitetens uddrivelse - Hansen, Nils Gunder (K&K - Kultur og Klasse, 2016)
The article investigates a historical development in the concepts of happiness and love and the norms of sexual behavior from a rural community over the upcoming welfare society in the suburbs to the late modern period in the big city. The changes are observed through three Danish literary texts from 1960, 1965 and 2011, first the novel I heltespor (“In the footsteps of heroes”) by Erik Aalbæk Jensen, then the short story Julestue (“The Christmas Gathering”) by Anders Bodelsen and finally the novel Se på mig (“Look at me”) by Kirsten Hammann. In the rural community happiness is knowing your right place and mastering the challenges of seduction and sexual temptation without the complete surrender to an inauthentic life of pure conventionalism. In the suburbs and early welfare society controlled infidelity with the exchange of partners represents a promise of happiness, something “more” and meaningful transcending the pure material satisfaction of the new and well managed consumer society. In the late modern period the importance of sexuality and love is downgraded in a remarkable manner: The search for happiness is extremely individualized and conceived as a kind of portal you have to enter at the precise right moment of your life trajectory. Sexuality and love seem to have lost their transcendent and integrational power in the game of happiness.